Mesenchymal stem cell therapy for intractable neonatal disorders - So Yoon Ahn; Won Soon Park; Se In Sung; Yun Sil Chang (Elsevier, 2021)
Mesenchymal stem cell (MSC) transplantation has emerged as a new promising therapeutic strategy for the treatment of intractable and devastating neonatal disorders with complex multifactorial etiologies, including bronchopulmonary dysplasia (BPD), intraventricular hemorrhage (IVH), and hypoxic-ischemic encephalopathy (HIE). In response to inflammatory and noxious environments, MSCs secrete various paracrine factors that perform several reparative functions, including exerting anti-inflammatory, anti-oxidative, anti-apoptotic, and anti-fibrotic effects, to enhance the regeneration of damaged cells and tissues. In this review, we summarize recent advances in stem cell research focusing on the use of MSCs in the prevention and treatment of newborn BPD, IVH and HIE, with particular emphasis on preclinical and clinical data.